The Optimization of Additional of Glycerol on the Biodegradable Foam from Corn Husk - Gani, Syefrin Syahadatia; Kusumayanti, Heny (Vocational College of Universitas Diponegoro, 2022)
Biodegradable foam is one of the packaging food friendly nature the environment. In process, biodegradable foam is still have low water absorpstion and low tensile strength. Biofoam made from raw starch and fiber have low tensile strength. Addition plasticizer material of glycerol can increase tensile strength on the biofoam. This research uses the baking process method. Based on research, biofoam with addition glycerol can affect the physical and mechanical characteristics of the biofoam produced. The optimum conditions for biofoam present in concentration 7% glycerol with value of the tensile strength 0.42 Mpa and value of power absorb water 35.07% and bidegradibility value in is 27.76% in 14 days. Glycerol can increase elasticity, because capable in reduce bond internal hydrogen so can decrease distance intermolecular, so that can increase value of the thensile strength. Variation condition operation influential on visuals and textures the resulting biofoam with optimum conditions 135℃ for 50 minutes. Temperature gelatinization starch sago 73 – 79℃. On this research, using variation temperature 115℃ and 135℃. And analysis result morphology show biofoam with high temperature have a high water absoprtion because if already pass temperature gelatinization starch so starch will form a paste and dissolve in water.